Instagram as a Catalyst for Descriptive Writing Development - Rahmawati, Suci; Sukarno, Berliana Sukma Tri (Journal of English Language and Education, 2025)
The increasing prevalence of social media use among students presents promising opportunities for the integration of digital platforms into language learning environments. Among these platforms, Instagram stands out due to its popularity and visual appeal. However, despite its widespread use in students’ daily lives, its potential as a pedagogical tool particularly for enhancing writing skills such as descriptive text remains largely untapped. This study was therefore conducted to investigate the effectiveness of Instagram as an online medium for teaching descriptive writing. Employing a quantitative research design, the study involved 34 tenth-grade students from SMA Negeri 8 Jambi, who were equally divided into an experimental group and a control group. A pre-test and post-test were administered to assess students’ writing performance before and after the treatment. The data revealed a significant improvement in the experimental group, with the average score increasing from 36.76 to 53.67. Furthermore, statistical analysis using an independent samples t-test confirmed a meaningful difference between the performance of the experimental and control groups. Based on these findings, it can be concluded that Instagram serves as an effective digital tool for enhancing students’ ability to write descriptive texts, demonstrating its value as a modern and engaging resource in English language instruction.